LIPID DISTRESS-SYNDROME AND PROSPECTS OF ITS CORRECTION BY STATINES - Tatiana Denisyuk; Galina Lazareva; Vladimir Provotorov (Belgorod National Research University, 2017)
Endothelial dysfunction in peritonitis: The formed concept of lipid distress syndrome (LDS) allows us to develop a working hypothesis on the key role of endothelial dysfunction in the aggressive development of atherosclerosis. The role of vascular endothelium in atherosclerosis: The process of NO production from L-arginine through eNOS involving tetrahydrobiopterin (BH4) is discussed. With the degradation of BH4 along the free radical path, an "eNOS uncouplation" (uncoupled eNOS). The clinical role of statins: Statins manifests itself by inhibiting the enzyme 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA reductase). Many large, randomized clinical trials have shown that lipid-lowering strategies that include statins have an anti-atherogenic potential. Pleiotropic effects of statins: Direct inhibition of small GTP-ase prenylation in vascular cells forms the essence of the hypothesis that explains the rapid pleiotropic effect of statins on the vascular wall, which does not depend on reducing lipid levels. Endogenous antioxidant defense systems: Effects of stasms. Statins have a beneficial effect on the vasculature not only by suppressing the prooxidant enzyme, but also by increasing the intensity and activity of endogenous antioxidant systems. The effect of statins on redox-sensitive transcritic pathways: One of the most important pathways is the NF-kB via the PI3K/Akt pathway. Experimental evidence of endothelioprotective properties of statins in the modeling of endotoxin-induced pathology: The use of HMG-CoA reductase inhibitors in the background of the fashion modeling endotoxin-induced pathology, leads to the development of a dose-dependent endothelioprotective effect, which is expressed in the normalization of QED, as well as the normalization of biochemical markers of inflammation (C-reactive protein) and the level of pro-inflammatory drugs. At the same time, positive dynamics of the final products of NO and eNOS expression was detected.